Transformasi Digital dan Inovasi Model Bisnis: Strategi Meningkatkan Kinerja Operasional Berkelanjutan Berbasis Kapabilitas Dinamis - Saputro, Adi; Riyadi, Selamet; David, David; Muhdaliha, Eryco (Indo-MathEdu Intellectuals Journal, 2025)
Digital transformation has become a core strategy to drive innovation and enhance operational performance in the era of technological disruption. This article aims to analyze the role of business digitalization in simultaneously promoting operational efficiency and business model innovation. Using a systematic literature review of more than 30 academic articles and cross-industry case studies, this study integrates the perspectives of dynamic capabilities, the balanced scorecard, and organizational ambidexterity as analytical frameworks. The findings indicate that the success of digitalization is largely determined by an organization's ability to integrate digital strategy into core business processes, develop sensing, seizing, and transforming capabilities, and balance exploration with exploitation. The study also reveals that implementing technologies such as Big Data Analytics, Artificial Intelligence, and the Internet of Things significantly improves production time efficiency, reduces costs, and enables the creation of new value propositions that better align with customer needs. However, the effectiveness of digital transformation also depends on transformational leadership, organizational culture readiness, and inclusive strategy orchestration. This article recommends an integrative approach to digital transformation, emphasizing sustainable operational excellence through data-driven innovation and adaptive business models.